Personalized Motor-Cognitive Exergame Training in Chronic Stroke Patients—A Feasibility Study - Huber, Simone K.; Held, Jeremia P. O.; de Bruin, Eling D.; Knols, Ruud H. (Frontiers in Aging Neuroscience, 2021)
Purpose: Exergame training may be beneficial for improving long-term outcome in stroke. Personalized training prescription applying progression rules, is missing. We adapted a theory-based taxonomy for a rehabilitation approach using user-centred exergames. The aims were primarily to investigate the feasibility of this rehabilitation approach, and secondarily to evaluate its performance of personalizing training progression, as well as explore the effects on secondary outcomes. Methods: Chronic stroke patients (≥ 18 years) were included, who were able to walk 10 meters and stand for 3 minutes. The rehabilitation approach was administered twice per week for eight weeks. As primary outcome, feasibility was evaluated by comparing achieved rates of recruitment, adherence, compliance, attrition, motivation, and satisfaction to pre-defined thresholds for acceptance. Secondary outcomes were (1) perceived motor and cognitive task difficulty throughout the intervention; (2) measures collected during baseline and post-measurements - a gait analysis, the Timed-up-and-go test (TUG), several cognitive tests assessing attentional, executive and visuospatial functions. Results: Thirteen patients (68.0 (49.5, 73.5) years, 34.5 (12.25, 90.75) months post-stroke) were included, of whom ten completed the study. Rates for inclusion (57%), adherence (95%), compliance (99%), motivation (77%) and satisfaction (74%) were acceptable, however, the attrition rate was too high (23%). The perceived motor and cognitive task difficulty predominantly moved below the targeted range. We found a significant change in the TUG (p = 0.05, r = 0.46) and medium-to-large effect sizes (p > 0.05) for swing time of the affected leg, the asymmetry index, time needed for the TMT A and accuracy for the TMT B and the MRT (0.26 ≤ r ≤ 0.46). Discussion: The intervention was feasible with minor modifications necessary, which warrants a larger trial investigating the effects of the rehabilitation approach following the adapted taxonomy on mobility, gait and cognitive functions. Two main limitations of the rehabilitation approach were; (1) the taxonomy decoupled motor and cognitive progression, which may be improper as motor and cognitive learning is coupled; (2) separate subjective ratings were used to guide the progression. Future studies should develop an instrument to objectively assess motor-cognitive task difficulty for monitoring the progression of an exergame-based training.